2015
DOI: 10.1007/s00467-015-3159-6
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, resilience and quality of life in children and adolescents with pre-dialysis chronic kidney disease

Abstract: Although patients and controls exhibited similar scores of resilience, CKD negatively impacted the QoL of pediatric patients, contributing to a higher frequency of depression and separation anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
5
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 48 publications
4
94
5
7
Order By: Relevance
“…Supporting the findings of the present research, existing studies reported resilience as a factor affecting HRQOL among healthy adolescents (Haase et al, 1999), adolescents with cancer (Wu et al, 2015), adolescents with pre-dialysis chronic kidney disease (Moreira et al, 2015) and adolescents with a chronic disease (Santos, de Matos, Simões, Leal, & do Céu Machado, 2017). To improve HRQOL among adolescents with a chronic health problem, enhancing resilience-the ability to obtain positive results in a disease-related stressful situation-is of immense importance regardless of cultural context.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Supporting the findings of the present research, existing studies reported resilience as a factor affecting HRQOL among healthy adolescents (Haase et al, 1999), adolescents with cancer (Wu et al, 2015), adolescents with pre-dialysis chronic kidney disease (Moreira et al, 2015) and adolescents with a chronic disease (Santos, de Matos, Simões, Leal, & do Céu Machado, 2017). To improve HRQOL among adolescents with a chronic health problem, enhancing resilience-the ability to obtain positive results in a disease-related stressful situation-is of immense importance regardless of cultural context.…”
Section: Discussionsupporting
confidence: 84%
“…There is international evidence that resilience is a major factor affecting HRQOL among adolescents with a chronic health problem (Moreira, Bouissou Morais Soares, Teixeira, Simoes, & Kummer, 2015). Resilience has been conceptualized as a dynamic process involving internal and external aspects that act to modify the effects of adverse life events (Rutter, 1999).…”
mentioning
confidence: 99%
“…CKD, even in mild stages [23] , has an impact on neurocognitive ability, health-related quality of life (HRQOL), and anxiety and depressive symptoms [24] . These issues cannot be ignored during the most important stages of development.…”
Section: Neurocognitive Impact and Quality Of Lifementioning
confidence: 99%
“…Future prospects regarding schooling and further education are poor if they are in need of dialysis—which is time consuming and often produces side effects. Significantly reduced quality of life is found among children with ESKD (Francis et al ), and in health‐related quality of life at all stages of chronic kidney disease (CKD) (Moreira et al ; Splinter et al ).…”
Section: Literature Reviewmentioning
confidence: 99%